LATOSOLS (OXISOLS) CARBON STORAGE IN NATURAL AND ALTERED MANAGEMENTS - Freitas, Ludmila de (2018)
The natural condition conversion of the soil to agriculture, highlighting to the sugarcane monoculture, imposes changes in the soil attributes. This work aimed to evaluate the variation of the carbon storage of Oxisols under native forest, sugarcane, and adjacent reforested area, in Guariba, SP state. In each area, four samples (composed of fifteen points) were randomly collected, at 0.0-0.10 and 0.10-0.20 m layers. We evaluated soil density, total porosity, grain size, organic matter content, total organic carbon, and total soil carbon storage of each sample, at 0.0-0.10 and 0.10-0.20 m. Data were submitted to analysis of variance, linear correlation, and multivariate analyzes. The results indicate that the carbon content is higher in the superficial layers in all three areas, decreasing in depth. The soil of the native forest area has the highest carbon storage, 20.65 Mg ha(-1), followed by reforestation and sugarcane cultivation areas, 15.93 and 13.71 Mg ha(-1) respectively at 0.0-0.10 m, and 17.71 Mg ha(-1), followed by reforestation and sugarcane cultivation areas, 14.86 and 12.06 Mg ha(-1) respectively at 0.10 -0.20 m. It was possible to verify, comparing to the native forest, the loss of carbon in the soil, losses of 22.9 and 33.6% in the reforested and cultivated with sugar cane areas, at 0.0-0, 10 m, and 31.9 and 16.1% in the reforested and cultivated with sugarcane areas at 0.10-0.20 m, respectively. Thus, we may conclude that the human intervention through agricultural practices reduces the carbon storage in the soil at lower levels than the ones found in native forest conditions.